(untitled) (REMUNOM, 2025)
This research aimed to analyze Indigenous school education in Itacoatiara, focusing on its legal precepts and its relationship with public policies regarding the provision and implementation of this educational modality. It sought to answer the following questions: How are the principles of intercultural, bilingual, specific, and differentiated Indigenous school education presented within the context of the municipality’s educational policies? What discourses emerge in the relationship between what is legally established and what is actually implemented? The study also aimed to understand whether the policies developed by SEMED/Itacoatiara recognize the need for specific, differentiated, and quality Indigenous education, and whether there are practical conflicts and contradictions to be overcome. The research followed a qualitative approach, using semi-structured interviews with coordinators and pedagogues from SEMED, as well as teachers working in schools located in Indigenous territories in the Rio Urubu communities. The interviews were conducted via video calls due to challenges encountered during the data collection period. The scientific initiation project titled “Intercultural, Bilingual, Specific, and Differentiated Indigenous School Education in the Context of Public Policies in Itacoatiara-AM” primarily aimed to identify the existing challenges to promoting quality Indigenous education, respecting the cultural and linguistic specificities of these communities. The data revealed normative advancements, but also significant gaps between legal guidelines and the realities experienced by the communities. This research contributes to the debate on the implementation of equitable Indigenous school education, emphasizing ethnic diversity and ensuring the rights of Indigenous peoples.